Effects of nitrogen addition and seasonal change on arbuscular mycorrhizal fungi community diversity in a poplar plantation - Peng, Sili; Ban, Mingjiang; Xing, Wei; Ge, Zhiwei; Mao, Lingfeng (Frontiers in Ecology and Evolution, 2022)
Arbuscular mycorrhizal (AM) fungi play a crucial role in carbon (C), nitrogen (N), and phosphorous (P) biogeochemical cycling. Therefore, it is essential to determine the seasonal responses of the AM fungal community to N addition to understanding better the ecological processes against a background of intensified N deposition. Based on an ongoing field simulation experiment with five N addition levels (0, 5, 10, 15, and 30 gN·m-2·a-1) in a 5-year-old poplar plantation at Dongtai Forest Farm in Yancheng, Jiangsu province, eastern China, soil physicochemical properties, the root colonization rate, and the rhizosphere soil AM fungal community diversity and composition in four seasons (summer, autumn, winter and spring) were investigated. Meanwhile, the relationships between the characteristics of the AM fungal community and soil environmental factors were analyzed. High-throughput sequencing showed that the dominant genera in the poplar plantation were Glomus (average relative abundance 87.52%), Diversispora (9.62%), and Acaulospora (1.85%). The addition of N significantly increased the root colonization rate in spring. The diversity of the AM fungal community (Chao and Shannon indexes) was primarily affected by seasonal change rather than N addition, and the diversity in summer was significantly lower than in the other three seasons. Redundancy analysis showed that soil temperature, available P, total P, and pH significantly affected the structure of the AM fungal community. It can be concluded N addition primarily influenced the root colonization rate, whereas seasonal change had a notable effect on the AM fungal community diversity. Although seasonal change and N addition greatly influenced the composition, seasonal change exerted a more substantial effect than N addition. These results will improve our understanding of the underground ecological processes in poplar plantation ecosystems.